Implementasi Pemasaran Syariah dalam Meningkatkan Penjualan pada Toko Kue UD. Rachbini - Mahmiyatus, Mahmiyatus; Ardyansyah, Farid (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
This study aims to analyze the implementation of the sharia marketing mix in increasing sales in micro-enterprises, using a case study of the UD. Rachbini cake shop. The approach used was descriptive qualitative, with data collection techniques such as in-depth interviews, direct observation, and documentation. The results show that the seven elements of the sharia marketing mix (namely: product, price, place, promotion, people, process, and physical evidence) have been implemented consistently and in line with Islamic principles. This implementation has had a positive impact on increasing sales and the store's annual turnover growth. This strategy also encouraged business expansion by opening new branches in the Pamekasan area. These findings reinforce that the sharia marketing approach not only has religious relevance but also can increase business competitiveness and sustainability. This study provides a practical contribution for MSMEs seeking to develop Islamic value-based strategies in the context of modern marketing.